Optimization of fenugreek and flax polysaccharides‐based edible coating formulation to preserve the quality and storability of apple after harvesting. Issue 10 (9th August 2020) - Rashid, Farhat; Ahmed, Zaheer; Hussain, Sarfraz; Kausar, Tusneem; Nadeem, Muhammad; Ainee, Ammara; Mehmood, Tahir
Abstract: The present study was designed to optimize the preparation conditions for fenugreek and flaxseed polysaccharides‐based edible composite coating blended with stearic acid and monoglycerides. Thirteen coating solutions were prepared according to the treatment plan generated by design expert software; applied the coating on apple fruit and stored at 20°C for 14 days. The effect of polysaccharides‐based coating on physicochemical parameters, for example, weight loss, firmness, titratable acidity (TA), pH, and total soluble solids (TSS) of apple was evaluated using response surface methodology (RSM). The results of RSM demonstrated non‐significant ( p  > .05) lack of fit for all response variables. Coefficients of determination ( R 2 ) ranging from .9498 to .9949 were obtained for these responses. From the response optimization analysis, a combination of 2.5 g fenugreek and 1.5 g flaxseed polysaccharide‐based coating was predicted to give desirable effects for all response variables. The findings of this study will be helpful for other researchers to understand the effect of fenugreek and flaxseed polysaccharides‐based coating formulations on response variables at linear, quadratic and interactive level. Practical applications: Edible coatings are gaining popularity compared to other types of packaging due to their more environmentally friendly nature and ability to carry active ingredients. Previously, no study was reported for the use of fenugreek and flaxseed‐based polysaccharide for preparation of edible coatings. The results of the present study showed that composite coatings contained 2.5 g fenugreek and 1.5 g flaxseed polysaccharides in combination were best for enhancing the postharvest quality and shelf life of apple. Because the study is based on RSM optimization of edible‐coating formulations, it helps predict the exact concentration of optimized component of a coating emulsion and its effect on the physiology of the fruit. This can help to formulate edible coatings on commercial basis, in the long run. In addition, this research can be repeated to reduce postharvest losses and complement economic benefits for other fruits and vegetables.